Rubidium intake in the adult population of the Omsk region - A. V. Brusentsova; D. V. Turchaninov; I. A. Sokhoshko; V. A. Shirinskiy (Фундаментальная и клиническая медицина)
Aim. To assess the nutritional consumption of rubidium in the adult population of the Omsk Region.Materials and Methods. Here we performed a cross-sectional study which included 421 individuals (177 men and 244 women) aged 18 to 83 years (median age 37 (23; 57) years). Rubidium consumption was determined by analysing the frequency of food intake and chemical composition of food consumed by the population of the Omsk Region.Results. Median daily rubidium intake was 1.1 mg/day (0.81; 1.48) that sufficiently exceeds minimum recommended dose (0.1 mg/day). We defined the reference range of rubidium intake as 1.1 (0.71 – 1.71) mg/day. Rubidium consumption tended to increase along with the population age, albeit no significant differences have been found between different age groups as well as between men and women. The most abundant rubidium sources were vegetables (55.6%) and beverages (29.6%). Among vegetables, the main sources of rubidium were onion (31.7%) and fresh tomatoes (20.7%), while tea was responsible for the majority (84.6%) of rubidium consumed from beverages. The proportion of vegetable-derived rubidium increased with age, in contrast to beverage-derived rubidium which demonstrated an opposite trend.Conclusion. The reference range of rubidium intake in the Omsk Region is 1.1 (0.71 – 1.71) mg/day. Rubidium intake does not depend on age and gender. The main sources of rubidium are vegetables and beverages.